Community and interweaving: The experience of feminist May 2018 in Chile - Hernández-Seguel, Fabiana (Acciones e Investigaciones Sociales, 2024)
This article aims to review the historicity of Chile and the social conflicts that arise today, placing special emphasis on the historical, but also emerging, demands of the feminist movement. To do this, we will address the social movement of 2018. In addition to its great capacity to attract people, it was led, organized and carried out by female students from diverse origins, many of them being first generation professionals. At the same time, the role of neoliberalism is explored, which emerged after the dictatorship in 1973. It allows us to understand the social unrest generated by structural inequality, which affects multiple areas of the social sphere. From there follows the discussion of how this has had an impact on the situation of women in the contemporary scenario and the challenges that arise, both for Latin American feminism and for feminism at a global level.
Keywords: Feminism; Chile; Latin America; Neoliberalism